Melatonin from Cerebrospinal Fluid but Not from Blood Reaches Sheep Cerebral Tissues Under Physiological Conditions. (March 2014) - Legros, C.; Chesneau, D.; Boutin, J. A.; Barc, C.; Malpaux, B.
<x xml:space="preserve">Abstract</x> The pineal gland secretes melatonin (MLT) that circulates in the blood and cerebrospinal fluid (CSF). We provide data to support the hypothesis that, in sheep and possibly in humans, only the CSF MLT, and not the blood MLT, can provide most of MLT to the cerebral tissue in high concentrations, particularly in the periventricular area. The MLT content of sheep brain, our chosen animal model, was found in significant concentration gradients oriented from the ventricle (close to the CSF) to the cerebral tissue, with concentrations varying by a factor of 1–125. The highest concentrations were observed close to the ventricle wall, whereas the lowest concentrations were furthest from the ventricles (407.0 ± 71.5 pg/ml compared to 84.7 ± 5.2 pg/ml around the third ventricle). This concentration gradient was measured in brain tissue collected at mid‐day and at the end of the night. Nocturnal concentrations were higher than daytime concentrations, reflecting the diurnal variation in the pineal gland. The concentration gradient was not detected when MLT was delivered to the brain via the bloodstream. The diffusion of MLT to cerebral tissues via CSF was supported by in vivo scintigraphy and autoradiography. 2‐[123I]‐MLT infused into the CSF quickly and efficiently diffused into the brain tissues, whereas [123I]‐iodine (control) was mostly washed away by the CSF flow and [123I]‐bovine serum albumin remained mostly in the CSF. Taken together, these data support a critical role of CSF in providing the brain with MLT.